THE RELATIONSHIP OF STRESS AND NUTRITIONAL STATUS WITH MENSTRUAL CYCLE IRREGULATION IN ADOLESCENTS - rini deska (Universitas Mitra Indonesia, 2021)
The menstrual cycle is the activity that occurs in the body before, during and between the menstrual cycle. Many factors affect the irregularity of the menstrual cycle, including stress and nutritional status. The purpose of this study was to examine the relationship between stress, nutritional status and menstrual cycle irregularities in adolescents. This study uses an analytical design with a cross sectional approach. The population in this study were all female students of Stikes Panca Bhakti Lampung. Data collection tool with a questionnaire. The sampling technique in this research is simple random sampling. The data analysis technique used in this research is univariate and bivariate data analysis with Chi-Square test. The results of the univariate analysis that experienced menstrual cycle irregularities in adolescents were 39 people (43.3%), experiencing stress as many as 49 people (54.4%), good nutritional status as many as 76 people (84.4%). The results of the bivariate analysis showed that there was a relationship between stress and menstrual cycle irregularities, p-value=0,000 and OR=12,031, there was a relationship between nutritional status and menstrual cycle irregularities with p-value=0,015 and OR=2,760. Suggestions, adolescents are expected to know the conditions of stress and nutritional status that can cause menstrual cycle irregularities for early anticipation. Keywords: Menstrual Cycle, Stress, Nutritional Status.